Comparative outcome of Thai pediatric osteosarcoma treated with two protocols: The role of high-dose methotrexate (HDMTX) in a single institute experience - Choeyprasert,W. (Asian Pacific Organization for Cancer Prevention, 2015)
Background: High-dose methotrexate (HD-MTX) is recognized as an efficient component of therapy against pediatric osteosarcoma in combination with other drugs such as cisplatin (CDP), carboplatin (CBDCA), doxorubicin (ADM), etoposide (VP-16) and ifosfamide (IFO). Objectives: To demonstrate the feasibility and effectiveness of the HD-MTX/CDP/DOX/VP-16/IFO [MTX(+)] protocol comparable to CDP/ADM/CBDCA/IFO [MTX(-)] for treating childhood osteosarcoma at Ramathibodi Hospital (1999-2014). Materials and Methods: A retrospective analysis was conducted of osteosarcoma patients aged less than 18 years treated with two chemotherapeutic regimens between 1999 and 2014. A total of 45 patients received the MTX(-) and 21 the MTX(+) protocol. Results: Overall limb-salvage and amputation rate were 12.9% and 77.7%, respectively. Kaplan-Meier analysis results for 3-year disease free survival (DFS) and overall survival (OS) regardless of treatment regimens were 43.4±6.0% and 53.2±6.1% respectively. The 3-year DFS and OS were improved significantly with the MTX(+) protocol compared to MTX(-) protocol (p = 0.010 and p = 0.009, log rank test) [69.8±10.5%, 79.8±9.1% for MTX(+) and 31.1±6.9%, 42.2±7.4% for MTX(-) protocol, respectively]. Patients with metastatic osteosarcoma treated with the MTX(+) protocol had statistically significant higher 3-year DFS and OS than those treated with the MTX(-) protocol (66.7±13.6% and 15.0±8.0% for 3-year DFS, p = 0.010, 73.3±13.2% and 20±8.9% for 3-year OS, p = 0.006, respectively). The independent risk factors for having inferior 3-year DFS and OS were poor histological response (tumor necrosis < 90%) and treatment with the MTX(-) protocol. The multivariate analysis identified only the treatment with the MTX(-) protocol as an independent predictor of inferior OS with a hazard ratio (HR) of 3.53 (95% confidence interval of 1.2-10.41, p = 0.022). Conclusions: Our study demonstrated the tolerability, feasibility and efficacy of the HDMTX-based regimen improving the survival rate in pediatric osteosarcoma cases, in line with reports from developed countries.